Morphological and Molecular Assessments of Bobtail Squids (Cephalopoda: Sepiolidae) Reveal a Hidden History of Biodiversity - Fernández-Álvarez, Fernando Á.; Sánchez, Pilar; Villanueva, Roger (Frontiers in Marine Science, 2021)
Molecular species delimitation assists taxonomic decisions for challenging species, like cryptic species complexes. Bobtail squids (Family Sepiolidae Leach, 1817) are a very diverse group of benthic and nektonic small to medium size cephalopods with many taxonomic questions to solve. In this study we provided new sequence data for 12 out 17 Mediterranean bobtail squid species including all the genera present in the area. Other relevant species from other parts of the world were used as comparison. The combined use of several molecular species delimitation methods consistently showed a picture of hidden biodiversity within this family which hinders the use of molecular data isolated from morphological characters. On the one hand, those methods consistently failed to accurately assessprovided contrasting results for the number of recognized species the actual biodiversity of some morphologically different specieswell-defined species. We suggest this can be an effect of a recent speciation phenomenon phenomena followed by an intense morphological drift. On the other hand, cryptic biodiversity was detected among members of several monophyletic clades assigned to the same nominal species, pointing to recent speciation phenomena without a parallel morphological evolution. Although Mediterranean bobtail biodiversity has been extensively studied for more than a century, a new species of Stoloteuthis Verrill, 1881 was discovered and described here, both using molecular and morphological methods. This new research stresses the necessity of combined morphological and molecular studies to correctly assess cephalopod biodiversity.